Defining the molecular blueprint that drives CD8+ T cell differentiation in response to infection - Turner, Stephen J.; Russ, Brendan E.; Denton, Alice E.; Hatton, Lauren; Croom, Hayley; Olson, Matthew R. (Frontiers in Immunology, 2012)
A cardinal feature of adaptive, cytotoxic T lymphocyte (CTL)-mediated immunity is the ability of naïve CTLs to undergo a program of differentiation and proliferation upon activation resulting in the acquisition of lineage-specific T cell functions and eventual establishment of immunological memory. In this review, we examine the molecular factors that shape both the acquisition and maintenance of lineage specific effector function in virus-specific CTL during both the effector and memory phases of immunity.